Does intervention sequence impact self-regulatory and behavioral outcomes in an adaptive trial among adults with prediabetes? - Carla K. Miller; Danielle King; Haikady N. Nagaraja; Kentaro Fujita; Jennifer S. Cheavens (Health Psychology and Behavioral Medicine)
Background: Lifestyle interventions can promote improvement in dietary intake and physical activity (PA), on average, by strengthening motivation, self-regulatory efforts, and commitment to behavioral change. However, maintenance of behavioral change is challenging, and slow responders during treatment often experience less overall success. Adaptive intervention sequences tailored to treatment response may be more effective in sustaining behavioral change.Methods: Adults ≥ 21 years old with prediabetes (n = 187) were stratified at week five to the standard Group Lifestyle Balance (GLB) intervention, if they achieved > 2.5% weight loss, or to the augmented intervention GLB Plus (GLB+) at week five, if they did not. At month five, each person in a matched pair was randomly assigned to GLB or GLB + for the extended intervention phase (months 5-12) followed by no study conduct (months 13-18). The primary comparison of interest was the change in outcomes between the standard (GLB followed by GLB) and augmented (GLB + followed by GLB+) intervention sequences post-intervention at 12 – and 18-months using linear mixed effect models.Results: The augmented GLB + intervention sequence reported a decline in the change in self-efficacy for reducing fat intake, self-efficacy for ‘sticking to’ healthy eating and exercise, and hopeful thought and planning compared to the standard GLB intervention sequence (all P < 0.0167) at 18-months. However, there were no significant differences between these intervention sequences at 18-months in the change in dietary intake or minutes of PA (all P > 0.05).Conclusions: No significant change in behavioral measures across intervention sequences occurred at study end. An 18-month decline in self-efficacy regarding diet and PA and hopeful thought and planning among slow responders following no intervention for six months indicates greater extended care is likely needed. The type of extended care that is most effective for slow treatment responders requires additional research.